2022
DOI: 10.1073/pnas.2116932119
|View full text |Cite
|
Sign up to set email alerts
|

Testing fractional doses of COVID-19 vaccines

Abstract: Due to the enormous economic, health, and social costs of the COVID-19 pandemic, there are high expected social returns to investing in parallel in multiple approaches to accelerating vaccination. We argue there are high expected social returns to investigating the scope for lowering the dosage of some COVID-19 vaccines. While existing evidence is not dispositive, available clinical data on the immunogenicity of lower doses combined with evidence of a high correlation between neutralizing antibody response and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Due to more rapid waning neutralizing antibody, dose-sparing strategy with intradermal booster vaccination should be used in the setting of inadequate vaccine supply. Fractional doses of COVID-19 vaccines could speed up vaccine coverages and save lives, even with lower efficacy, especially in the era of omicron pandemic [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to more rapid waning neutralizing antibody, dose-sparing strategy with intradermal booster vaccination should be used in the setting of inadequate vaccine supply. Fractional doses of COVID-19 vaccines could speed up vaccine coverages and save lives, even with lower efficacy, especially in the era of omicron pandemic [43] .…”
Section: Discussionmentioning
confidence: 99%
“…A low-dose BNT162b2 booster after AZD1222 also showed lower adverse events, e.g., fatigue, fever, and local reaction, than the standard-dose booster [16]. Based on the correlation between neutralizing antibody titers and vaccine efficacy against symptomatic infection [17], a model using data from dose-finding trials suggested that half or one-fourth doses of mRNA-1273 have 90 to 95% efficacy, similar to a standard dose [18]. One-third and two-third doses of BNT162b2 also showed predicted efficacy of 70 to 85%, compared with 95% for a standard dose [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the correlation between neutralizing antibody titers and vaccine efficacy against symptomatic infection [17], a model using data from dose-finding trials suggested that half or one-fourth doses of mRNA-1273 have 90 to 95% efficacy, similar to a standard dose [18]. One-third and two-third doses of BNT162b2 also showed predicted efficacy of 70 to 85%, compared with 95% for a standard dose [18]. Using a fractional dosing strategy might ease the limited vaccine supply, thus speeding up vaccine coverage and reducing mortality, even if it yields lower efficacy [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allocation design has led to discussion on optimal strategies going forward for COVID-19 vaccine and other vaccine distribution for the U.S., and the optimal design of vaccine allocation mechanisms in general (Press, Huisingh-Scheetz, and Arora 2021;Agarwal et al 2021;Cole 2021;Guo et al 2021;Więcek et al 2022).…”
Section: Introductionmentioning
confidence: 99%